Exploring the Future of Solar Stills: Recent Breakthroughs in Performance Enhancement - Almajali T.A.H.; Ismail F.B.; Gunnasegaran P.A.L.; Al Shurafa S.M.; Kazem H.A. (Taylor and Francis Ltd., 2025)
Water scarcity presents a pressing global challenge, particularly in regions facing rising demands amidst diminishing freshwater resources. This research investigates the efficiency and freshwater production of solar desalination systems, focusing on both passive and active distillation methods. While previous studies have highlighted advancements in solar still technologies, this review critically assesses their performance based on criteria such as productivity, efficiency, and water production costs. Key findings indicate that double-slope solar stills exhibit 50% improvements in daily water output compared to passive variants. Additionally, active solar stills incorporating the Parabolic Trough Collectors technology demonstrate the highest productivity, achieving 12.4 L/m2 per day. The integration of supplementary purification technologies, including optical upgrades and nanomaterials, further enhances the solar still thermal properties and efficiency. Remarkably, the Hybrid Solar Still achieves the lowest recorded water cost ($0.009 per L), underscoring the economic viability of solar desalination. Addressing scientific gaps, this study emphasizes the importance of concurrently maximizing freshwater production and efficiency in solar desalination designs, calling for integrated approaches that leverage concentrated solar energy for sustainable water provision. ? 2024 Taylor & Francis Group, LLC.